If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6)(x + -2)(x + 3) = 264 Reorder the terms: (6 + x)(x + -2)(x + 3) = 264 Reorder the terms: (6 + x)(-2 + x)(x + 3) = 264 Reorder the terms: (6 + x)(-2 + x)(3 + x) = 264 Multiply (6 + x) * (-2 + x) (6(-2 + x) + x(-2 + x))(3 + x) = 264 ((-2 * 6 + x * 6) + x(-2 + x))(3 + x) = 264 ((-12 + 6x) + x(-2 + x))(3 + x) = 264 (-12 + 6x + (-2 * x + x * x))(3 + x) = 264 (-12 + 6x + (-2x + x2))(3 + x) = 264 Combine like terms: 6x + -2x = 4x (-12 + 4x + x2)(3 + x) = 264 Multiply (-12 + 4x + x2) * (3 + x) (-12(3 + x) + 4x * (3 + x) + x2(3 + x)) = 264 ((3 * -12 + x * -12) + 4x * (3 + x) + x2(3 + x)) = 264 ((-36 + -12x) + 4x * (3 + x) + x2(3 + x)) = 264 (-36 + -12x + (3 * 4x + x * 4x) + x2(3 + x)) = 264 (-36 + -12x + (12x + 4x2) + x2(3 + x)) = 264 (-36 + -12x + 12x + 4x2 + (3 * x2 + x * x2)) = 264 (-36 + -12x + 12x + 4x2 + (3x2 + x3)) = 264 Combine like terms: -12x + 12x = 0 (-36 + 0 + 4x2 + 3x2 + x3) = 264 (-36 + 4x2 + 3x2 + x3) = 264 Combine like terms: 4x2 + 3x2 = 7x2 (-36 + 7x2 + x3) = 264 Solving -36 + 7x2 + x3 = 264 Solving for variable 'x'. Reorder the terms: -36 + -264 + 7x2 + x3 = 264 + -264 Combine like terms: -36 + -264 = -300 -300 + 7x2 + x3 = 264 + -264 Combine like terms: 264 + -264 = 0 -300 + 7x2 + x3 = 0 The solution to this equation could not be determined.
| 3*5m-3= | | 4k-2k=-20 | | g=7f+h | | x+5=2y-20 | | y=-3x^4-18x^3-24x^2 | | 3-3*6+2=23 | | 3m^2-11m-60=0 | | 5+4m=37 | | 21=x+14+x+11 | | 0.666(x+6)=-18 | | 2x+2.50=10.50 | | 17=x+15+x+22 | | .15+.4x=.7x-.03 | | X-0.3(X)=10500 | | x-0.3x=10500 | | 14x=2x+1+11 | | 16=x+9+x+17 | | 24-x+2x=53 | | x^4+4x^3-16x-16=0 | | 3y+4=50 | | 19=2x-14+2x-15 | | X-.3x=10500 | | 0.24=x-x^2 | | 18=12+x+x+6 | | -x^2-18=90 | | 18x^3+3x^2-x=0 | | n^2-5n-10=-11 | | 4y+5+3y= | | 2x+7-7=-39 | | ln(x+4)+7=32 | | X^2+18x=-90 | | 13=x+17+x+10 |